2002
DOI: 10.1034/j.1600-6143.2002.20604.x
|View full text |Cite
|
Sign up to set email alerts
|

Inability to Induce Tolerance Through Direct Antigen Presentation

Abstract: Both the direct and indirect antigen presentation pathways are important mechanisms for T cell-mediated allograft rejection. Studies using knockout mice and monoclonal antibodies have demonstrated that CD4π T cells are both necessary and sufficient for the rejection of allogeneic tissues, including skin, heart, and islet. Furthermore, combined blockade of the CD28/B7 and CD154/CD40 costimulatory pathways induces tolerance in multiple CD4π T-cell dependent allograft models. In this study, we addressed the T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…Our finding that primary CD4 + T-cell expansion in vivo was inhibited by CTLA4Ig is consistent with the reported effects of CTLA4Ig on T-cell proliferation using the OVA TCR-tg model (26). Furthermore, Rulifson et al (10) have recently demonstrated that in the ABM TCR-tg system combined anti-B7-1 mAb and anti-B7-2 mAb blockade inhibits TCR-tg CD4 + T-cell division in response to direct antigen presentation in vitro. Our results also provide further evidence for functional inhibition of alloantigen-reactive cells following CTLA4Ig administration in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that primary CD4 + T-cell expansion in vivo was inhibited by CTLA4Ig is consistent with the reported effects of CTLA4Ig on T-cell proliferation using the OVA TCR-tg model (26). Furthermore, Rulifson et al (10) have recently demonstrated that in the ABM TCR-tg system combined anti-B7-1 mAb and anti-B7-2 mAb blockade inhibits TCR-tg CD4 + T-cell division in response to direct antigen presentation in vitro. Our results also provide further evidence for functional inhibition of alloantigen-reactive cells following CTLA4Ig administration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in vivo studies have been limited to using MHC class I-alloreactive TCR-tg systems in which the alloimmune response is mediated by CD8 + T cells (5)(6)(7)(8), or to using antigen-specific rather than allospecific CD4 + TCR-tg animals as surrogates (9). Recently, a novel TCR-tg MHC class II-alloreactive transplantation model has been described (10,11). The anti-bm12 (ABM) TCR-tg mouse (12) expresses a TCR that utilizes the Va2.1 and Vb8.1 chains and specifically recognizes the MHC class II molecule I-A bm12 found on B6.C-H2bm12/KhEg (bm12) mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study showed that LCs can induce T cells to reach an activation threshold that is sufficient for transplant rejection in the absence of a costimulatory signal or under the condition of impaired NF-jB pathway, which indicates that LCs can prime T cells through a bypass signal pathway (Molinero et al 2008;Rulifson et al 2002). This finding may explain why certain immune inhibitors, such as rapamycin, which target NF-jB, do not display the expected effects in skin transplantation models that have abundances of LCs (Sun et al 2008).…”
Section: The Immune Effects Of Dendritic Cells In Skin Graftsmentioning
confidence: 99%
“…This model was not associated with GVHD as measured by examination of intestines, liver, skin, or other tissues (Liu et al, 2007). Rulifson et al (2002) demonstrated that Langerhans cells resident in the skin of the donor were such effective antigen presenting cells (APCs) that they could prime T cells for activation independently of either the B7 or CD40 activation pathways. In their hands, the strength of this direct antigen presentation reaction limited the success of tolerance induction mediated through the interruption of either B7-CD28 or CD40-CD154 pathway.…”
Section: The B7/cd28 Pathway and Skin Graftsmentioning
confidence: 99%